Identification and analysis of public policies and social actors for child population with disabilities in Colombia - Tróchez, Claudia Patricia; Patarroyo, Diana Carolina (Universidad Distrital Francisco José de Caldas, 2016)
This research focuses on the situation of boy and girls less than 6 years old with disabilities and the role of different social ac- tors with respect to public policies for the integral care of this population. For this purpose, we applied a mixed methodology involving both, an analysis of ofﬁcial statistics and documentary research. As a main ﬁnding, we veriﬁed that a fragmented approach in the design of public policies for disabled children prevails in the attention of this population and their families.